Trần Đức Thảo: A Marxist Theory of the Origins of Human Language - D’Alonzo, Jacopo (Theoria et Historia Scientiarum, 2016)
This paper will explore Trần Đức Thảo’s (Từ Sơn, Bắc Ninh, September 26th, 1917 – Paris, April 24th, 1993) work from historical, philosophical, and linguistic points of view. Most notably it will focus on Thảo’s Recherches sur l’origine du langage et de la conscience (1973). According to Marx and Engels, Thảo argued that language was originally constituted during collective cooperative activities. And he also suggested that human specific skills appeared for the first time with the production of first tools. To him, language arose as gestural and verbal indication involved in task-oriented cooperative activities already in hominid societies. Trying to integrate Piaget’s child development psychology with the findings of Spirkin’s anthropology, Thảo described six stages of evolution of genus Homo.